The Role of Bahtsul Masail in the Development of Contemporary Islamic Jurisprudence in Indonesia: Peran Bahtsul Masail dalam Perkembangan Fikih Islam Kontemporer di Indonesia - Adi Susandi; Ending Solehudin; Syahrul Anwar; Dede Sudrajat (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This article explores the evolving role of Bahtsul Masail, an Islamic legal forum under Nahdlatul Ulama (NU), in shaping contemporary Islamic jurisprudence in Indonesia. Bahtsul Masail has historically functioned as a platform for collective ijtihad, enabling scholars to address modern socio-religious issues using a structured legal reasoning method rooted in classical fiqh. The objective of this paper is to examine how Bahtsul Masail has transitioned from a textual and conservative framework toward a more dynamic, inclusive, and contextually responsive model of Islamic legal interpretation. Utilizing a qualitative-descriptive method, the research analyzes primary documents from NU congresses and scholarly literature. The findings reveal that Bahtsul Masail promotes a three-tiered methodological approach qauliy, ilhaqiy, and manhajiy allowing legal rulings to balance orthodoxy with socio-legal adaptability. This transformation not only strengthens the legitimacy of Islamic legal authority in Indonesia’s pluralistic society but also provides a model for legal innovation within traditional Islamic institutions.